Failure analysis and damage prevention on offshore pipelines under extreme loadings - Zhang, Yanmei (2016)
Offshore pipelines, generally constructed by girth welding method, are one of major transportation tools for the natural resources. Some flaws, such as surface cracks or embedded cracks, may be introduced into the welds during construction. The potential flaws under large plastic deformation will seriously threaten the structural reliability of offshore pipelines. Therefore, the main objectives of this PhD research project is to investigate the nonlinear elastic-plastic fracture behaviors of offshore pipelines subjected to extreme loading conditions, such as large plastic bending and fatigue loadings. Extensive fracture analyses of pipeline girth welds with 3-D semi-elliptical surface cracks and elliptical embedded cracks are systematically performed. Comparisons of fracture toughness obtained by BS7910:2005 and current results indicate that the BS7910 code may produce highly conservative prediction of fracture. Based on investigations of the fracture responses of flawed offshore pipelines, failure assessment diagrams (FAD) are proposed for preliminary evaluations of the fracture capacity.